Regional Impact of a CRE Intervention Targeting High Risk Postacute Care Facilities (Chicago PROTECT). (October 2020) - Lin, Michael; Froilan, Mary Carl; Makhija, Jinal; Benson, Ellen; Bartsch, Sarah; Bell, Pamela B.; Black, Stephanie; Burdsall, Deborah; Ealy, Michelle; Fiore, Anthony; Foy, Sharon; Frias, Mabel; et al.
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) are endemic in the Chicago region. We assessed the regional impact of a CRE control intervention targeting high-prevalence facilities; that is, long-term acute-care hospitals (LTACHs) and ventilator-capable skilled nursing facilities (vSNFs). Methods: In July 2017, an academic–public health partnership launched a regional CRE prevention bundle: (1) identifying patient CRE status by querying Illinois' XDRO registry and periodic point-prevalence surveys reported to public health, (2) cohorting or private rooms with contact precautions for CRE patients, (3) combining hand hygiene adherence, monitoring with general infection control education, and guidance by project coordinators and public health, and (4) daily chlorhexidine gluconate (CHG) bathing. Informed by epidemiology and modeling, we targeted LTACHs and vSNFs in a 13-mile radius from the coordinating center. Illinois mandates CRE reporting to the XDRO registry, which can also be manually queried or generate automated alerts to facilitate interfacility communication. The regional intervention promoted increased automation of alerts to hospitals. The prespecified primary outcome was incident clinical CRE culture reported to the XDRO registry in Cook County by month, analyzed by segmented regression modeling. A secondary outcome was colonization prevalence measured by serial point-prevalence surveys for carbapenemase-producing organism colonization in LTACHs and vSNFs. Results: All eligible LTACHs (n = 6) and vSNFs (n = 9) participated in the intervention. One vSNF declined CHG bathing. vSNFs that implemented CHG bathing typically bathed residents 2–3 times per week instead of daily. Overall, there were significant gaps in infection control practices, especially in vSNFs. Also, 75 Illinois hospitals adopted automated alerts (56 during the intervention period). Mean CRE incidence in Cook County decreased from 59.0 cases per month during baseline to 40.6 cases per month during intervention ( P < .001). In a segmented regression model, there was an average reduction of 10.56 cases per month during the 24-month intervention period ( P = .02) (Fig. 1), and an estimated 253 incident CRE cases were averted. Mean CRE incidence also decreased among the stratum of vSNF/LTACH intervention facilities ( P = .03). However, evidence of ongoing CRE transmission, particularly in vSNFs, persisted, and CRE colonization prevalence remained high at intervention facilities (Table 1). Conclusions: A resource-intensive public health regional CRE intervention was implemented that included enhanced interfacility communication and targeted infection prevention. There was a significant decline in incident CRE clinical cases in Cook County, despite high persistent CRE colonization prevalence in intervention facilities. vSNFs, where understaffing or underresourcing were common and lengths of stay range from months to years, had a major prevalence challenge, underscoring the need for aggressive infection control improvements in these facilities. Funding: The Centers for Disease Control and Prevention (SHEPheRD Contract No. 200-2011-42037) Disclosures: M.Y.L. has received research support in the form of contributed product from OpGen and Sage Products (now part of Stryker Corporation), and has received an investigator-initiated grant from CareFusion Foundation (now part of BD).